2023
DOI: 10.1007/s10072-022-06579-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between temporal patterns of baroreflex sensitivity after traumatic brain injury and prognosis: a preliminary study

Abstract: Introduction Traumatic brain injury (TBI) may lead to an increase in intracranial pressure (ICP) as well as impairment of cerebral vascular reactivity and the autonomic nervous system. This study aimed to investigate individual patterns of changes in baroreflex sensitivity (BRS) along with the assessment of pressure reactivity index (PRx) and ICP after TBI. Materials and methods Twenty-nine TBI patients with continuous arterial blood pressure (ABP) and ICP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Some patients in our study received administration of vasopressors at individually adjusted dosages to regulate ABP. Although, applied pharmaceutical treatment by anesthetics (mainly propofol) and vasopressors can affect both CA and BRS test results by blocking the cardiovascular reflex response [ 40 ] or affecting cerebrovascular reactivity [ 41 , 42 ], however, recent study showed that propofol did not produce a significant alteration in the average heart rate, which serves as the basis for measuring baroreflex sensitivity [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some patients in our study received administration of vasopressors at individually adjusted dosages to regulate ABP. Although, applied pharmaceutical treatment by anesthetics (mainly propofol) and vasopressors can affect both CA and BRS test results by blocking the cardiovascular reflex response [ 40 ] or affecting cerebrovascular reactivity [ 41 , 42 ], however, recent study showed that propofol did not produce a significant alteration in the average heart rate, which serves as the basis for measuring baroreflex sensitivity [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using synchronized, predefined changes in blood pressure and heart rate, the multimodal system can continuously monitor the patient's BRS. 22,[32][33][34] With hyperemia and/or ischemia associated with secondary injury and unfavorable outcomes, decreased BRS has also been associated with poor outcomes. 22,32,34 In addition to BRS, HRV can also be monitored with the multimodal system to assess central autonomic regulation, because a TBI can result in autonomic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…22,[32][33][34] With hyperemia and/or ischemia associated with secondary injury and unfavorable outcomes, decreased BRS has also been associated with poor outcomes. 22,32,34 In addition to BRS, HRV can also be monitored with the multimodal system to assess central autonomic regulation, because a TBI can result in autonomic dysfunction. Using the R-to-R pattern of an electrocardiogram, fluctuations between heartbeats are analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, TBI, depending on the cerebral location, if the injury was localized to one cerebral location or diffuse across several, and injury severity, can result in axonal injury [81], neurovascular detriments [82], electrophysiological changes [83], and an uncoupling between the cardiovascular and autonomic nervous system [84]. The neuroanatomical disruptions from TBI have been linked to the development of PD [59], anduncoupling of autonomic control over the cardiovascular system can lead to reduced baroreflex sensitivity [85], thereby linking TBI to hypertension. Due to the prevalence of PD among veterans [52][53][54][55]86] and the growth in the number of veterans who have experienced TBI in recent years [57], the presence of PD and/or TBI among veterans appears to be an important factor for hypertension among these individuals.…”
Section: Plos Onementioning
confidence: 99%